(untitled) - Chang, Raymond (Boston, MA, 2005)
This revision of an introductory chemistry text features balanced coverage of theoretical and descriptive chemistry. New to this edition are 22 more "Chemistry in Action" essays, 664 review questions, and 247 end-of-chapter miscellaneous problems. Thermochemistry is now covered in the text, immediately following Stoichiometry. An organic chapter on polymer chemistry has also been added.
Keywords: Chemistry